Power electronic transformers – is it the future of power systems? - Strzelecki, R. (Технічна електродинаміка, 2012)
It is well known that traditional networks transformers are difficult to control as well as they increase in a significant way the size of coupling AC installations. Moreover, in no-load running they generate relatively high reactive power and may cause voltage distortion. These factors and other observed trends associated with change toward application of Smart Grids raised interest in promoting Electronics Power Interfaces for AC systems. This paper presents the idea a special kind of EPI equipments – Power Electronics Transformers.